2007
DOI: 10.1016/s0929-6646(09)60214-x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Apoptosis Induced by Fungal Immunomodulatory Peptide-fve via Reducing IL-5α Receptor

Abstract: The results suggest that FIP-fve can inhibit IL-5-mediated survival of eosinophils through the modulation of cytokine receptor expression and apoptotic signal protein production. The modulatory effect of FIP-fve on eosinophil apoptosis in vitro indicates that it may have some therapeutic effect on eosinophil-related allergic inflammation in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…These findings were then followed by several studies investigating the anti-allergic effect of FIP-fve against allergen-induced airway diseases (Hsieh et al, 2007; Lee et al, 2013). Hsieh et al (2007) investigated the effect of FIP-fve on the survival of eosinophils isolated and purified from allergic asthmatic patients in the presence of IL-5.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings were then followed by several studies investigating the anti-allergic effect of FIP-fve against allergen-induced airway diseases (Hsieh et al, 2007; Lee et al, 2013). Hsieh et al (2007) investigated the effect of FIP-fve on the survival of eosinophils isolated and purified from allergic asthmatic patients in the presence of IL-5.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 95%
“…Hsieh et al (2007) investigated the effect of FIP-fve on the survival of eosinophils isolated and purified from allergic asthmatic patients in the presence of IL-5. The study indicated that FIP-fve induced apoptosis of eosinophils in the presence of IL-5 (which is a survival factor of eosinophils), thereby preventing eosinophils from undergoing necrosis.…”
Section: Biological Activities Of F Velutipesmentioning
confidence: 99%
“…Fve was able to induce mitogenic proliferation of human peripheral mononuclear cells (PBMCs) and enhance mRNA transcription of interleukin (IL)-2 and interferon (IFN)-c in vitro (Ko et al 1995;Wang et al 2004). Administration of Fve with allergens either intraperitoneally, orally, or intranasally inhibited allergeninduced systemic anaphylactic responses (Ko et al 1995), food allergic reactions (Hsieh et al 2003), or allergic airway inflammation (Liu et al 2003;Liu and Tsai 2005;Hsieh et al 2007) in vivo, respectively. Recently, Fve has also been shown to exhibit potent adjuvant properties that enhanced the immunogenicity of the human papillomavirus type-16 (HPV-16) E7 oncoprotein and conferred increased antitumor effects against the inoculation of HPV-16 E7-expressing TC-1 cells in a mouse model (Ding et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the immunoprophylatic effects of FVE in Th2-mediated allergic anaphylaxis were associated with the ability of FVE to enhance activation of IFN-γ-releasing Th1 cells and inhibit IL-5-mediated survival of eosinophils [9,11]. IFN-γ was believed to play a key role in FVE-mediated immune response, leading to subsequent priming of the Th1 differentiation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%